Kajian Ergonomi pada Alat dan Perlengkapan TNI dalam Rangka Mendukung Kepentingan Pertahanan Negara - Ainun Habibah; Hardianto Iridiastadi; Sigit Permana (Universitas Mercu Buana, 2021)
This study purpose to determine the feasibility and ergonomics aspects of the P-1 and Ranpur Panser APS 1 6X6 produced by PT. Pindad. The data was collected using a survey method through filling out a questionnaire with a purposive sampling method, interviews, and observations. Questionnaires were distributed to 350 TNI soldiers for the use of the P-1 Pistol and 180 of the TNI soldier. Measurement of anthropometric data and fatigue of Ranpur Panser APS soldiers was carried out on 30 soldiers who were randomly drawn from 180 soldiers. The results showed that the Pistol P-1 produced by PT. Pindad in general was still safe, comfortable, and accurate to shoot. However, the addition of infrared will make it easier for soldiers to shoot the targets. The results of the research on the application of ergonomic aspects at Ranpur Panser APS 1 6X6 resulted in a value of 57.47% for the effective criteria, 66.83% for the safe criteria, 69.56% for the comfortable criteria, 75.83% for the healthy criteria, and 80.17% for the efficient criteria. The results show that Ranpur Panser APS fulfill overall EASNE aspects with several notes discussed. Related to the fatigue test, results obtained a significance value of 0.01<0.05 which indicates a significant correlation between fatigue before and after using Ranpur Panser APS 1 6X6.